Effects of simulated spring thaw of permafrost from mineral cryosol on CO2 emissions and atmospheric CH4 uptake. Issue 9 (11th September 2015) - Stackhouse, Brandon T.; Vishnivetskaya, Tatiana A.; Layton, Alice; Chauhan, Archana; Pfiffner, Susan; Mykytczuk, Nadia C.; Sanders, Rebecca; Whyte, Lyle G.; Hedin, Lars; Saad, Nabil; Myneni, Satish; Onstott, Tullis C.
Abstract: Previous studies investigating organic‐rich tundra have reported that increasing biodegradation of Arctic tundra soil organic carbon (SOC) under warming climate regimes will cause increasing CO2 and CH4 emissions. Organic‐poor, mineral cryosols, which comprise 87% of Arctic tundra, are not as well characterized. This study examined biogeochemical processes of 1 m long intact mineral cryosol cores (1–6% SOC) collected in the Canadian high Arctic. Vertical profiles of gaseous and aqueous chemistry and microbial composition were related to surface CO2 and CH4 fluxes during a simulated spring/summer thaw under light versus dark and in situ versus water saturated treatments. CO2 fluxes attained 0.8 ± 0.4 mmol CO2  m −2  h −1 for in situ treatments, of which 85 ± 11% was produced by aerobic SOC oxidation, consistent with field observations and metagenomic analyses indicating aerobic heterotrophs were the dominant phylotypes. The Q10 values of CO2 emissions ranged from 2 to 4 over the course of thawing. CH4 degassing occurred during initial thaw; however, all cores were CH4 sinks at atmospheric concentration CH4 . Atmospheric CH4 uptake rates ranged from −126 ± 77 to −207 ± 7 nmol CH4  m −2  h −1 with CH4 consumed between 0 and 35 cm depth. Metagenomic and gas chemistry analyses revealed that high‐affinity Type II methanotrophic sequence abundance and activity were highest between 0 and 35 cm depth. Microbial sulfate reduction dominated the anaerobic processes, outcompeting methanogenesis for H2 and acetate. Fluxes, microbial community composition, and biogeochemical rates indicate that mineral cryosols of Axel Heiberg Island act as net CO2 sources and atmospheric CH4 sinks during summertime thaw under both in situ and water saturated states. Key Points: Arctic mineral cryosols oxidize atmospheric CH4 under saturated and dry states CO2 emissions result of aerobic heterotrophy and governed by water saturation Permafrost thaw increases cumulative carbon loss of soils up to a factor of 3